Scalogram-Based Multiclass Fetal State Classification Using Expert-Annotated CTG and SE-ResNet-50 - Kadarina, Trie Maya; Basari, Basari; Gunawan, Dadang; Auzan, Abraham (Informatica, 2025)
Accurate classification of cardiotocographic (CTG) signals plays a critical role in the early detection of fetal health conditions, enabling timely and appropriate medical interventions. A more precise understanding of cardiotocography patterns, particularly in suspicious cases, can help minimize unnecessary interventions and reduce healthcare costs. This study proposes a multiclass classification framework using 552 expert-annotated CTG records containing fetal heart rate (FHR) and uterine contraction (UC) signals. Time-domain augmentation, including cyclic temporal shifting, Gaussian noise, and segmented Gaussian noise, was applied to address class imbalance. The augmented FHR and UC signals were then transformed into scalograms using Continuous Wavelet Transform (CWT), producing dual-channel RGBencoded images. Data were split into 90% for stratified five-fold cross-validation and 10% for independent testing. The proposed ResNet50, enhanced with SE-based channel attention and dropout layers, was compared against several baselines, including CNN, MobileNet, EfficientNet-B0, ResNet18, and ResNet50. It achieved the best performance with an F1-score of 0.7267 and AUC of 0.7489 on the test set, outperforming all baselines. These results highlight its potential for integration into intelligent clinical decision support systems in prenatal care.